PET imaging of glucose metabolism, neuroinflammation and demyelination in the lysolecithin rat model for multiple sclerosis. (October 2014) - de Paula Faria, Daniele; de Vries, Erik FJ; Sijbesma, Jurgen WA; Buchpiguel, Carlos A; Dierckx, Rudi AJO; Copray, Sjef CVM
Background: Injection of lysolecithin in the central nervous system results in demyelination accompanied by local activation of microglia and recruitment of monocytes. Positron-emission tomography (PET) imaging, using specific tracers, may be an adequate technique to monitor these events in vivo and therefore may become a tool for monitoring disease progression in multiple sclerosis (MS) patients. Objectives: The objective of this paper is to evaluate the potential of PET imaging in monitoring local lesions, using [ 11 C]MeDAS, [ 11 C]PK11195 and [ 18 F]FDG as PET tracers for myelin density, microglia activation and glucose metabolism, respectively. Methods: Sprague-Dawley rats were stereotactically injected with either 1% lysolecithin or saline in the corpus callosum and striatum of the right brain hemisphere. PET imaging was performed three days, one week and four weeks after injection. Animals were terminated after PET imaging and the brains were explanted for (immuno)histochemical analysis. Results: PET imaging was able to detect local demyelination induced by lysolecithin in the corpus callosum and striatum with [ 11 C]MeDAS and concomitant microglia activation and monocyte recruitment with [ 11 C]PK11195. [ 18 F]FDG imaging demonstrated that glucose metabolism was maintained in the demyelinated lesions. Conclusion: PET imaging with multiple tracers allows simultaneous in vivo monitoring of myelin density, neuroinflammation and brain metabolism in small MS-like lesions, indicating its potential to monitor disease progression in MS patients.